Descriptive Epidemiology of the Tuberculosis Service Delivery Project Beneficiaries in Northwest Syria: 2019-2020 - Alashavi, Hani; Daher, Mahmoud; Chorgoliani, Dato; Saflo, Molham; Zeidan, Mohammed; Huseyinibrahim, Fedi; Ismail, Eyup; Yousef, Abdul Raouf Haj; Ayat, Khalil; Elobayd, Ekrem; Dadu, Andre; Shaikh, Masood Ali (Frontiers in Public Health, 2021)
Background: Tuberculosis (TB) is a chronic communicable disease caused by Mycobacterium tuberculosis that thrives in protracted humanitarian crises. It is an important cause of morbidity and mortality burden in the developing world. Methods: in April 2019, the World Health Organization’s (WHO) country office of Turkey started three TB centers in the cities of A’zaz, Idleb, and Afrin in northwest Syria, to provide the population with quality TB treatment curative services. The objectives of the project involved provision of full package of TB services in alignment with WHO TB standards and protocols. Three contractors i.e. national NGOs were selected after a rigorous process in accordance with WHO policies. These newly established centers were equipped with the essential medical supplies, including well-functioning X-ray and microscopy laboratories run by WHO-trained medical doctors and lab technicians. Results: Based on the quarterly reports submitted by the WHO partners, from the last two quarters of the year 2019, and the four quarters for the year 2020, out of 785 cases diagnosed by either by clinical, laboratory and radiological assessment, 251 cases were bacteriologically confirmed as TB cases against the backdrop of 2236 bacteriological investigations done and on a weekly average of 31 sputum specimens processed. A total of 316 smear positive slides were identified during the study period, with the proportion of smear positive slides to be 14.13%. Clinical status determined after 6-month of treatment revealed that out of the181 patients enrolled in the third quarter of 2019, 128 patients either were cured or successfully completed their TB treatment; with a treatment success rate of 70.7% and in quarter 4, 2019 those figures were respectively: 133, 82 and 61.7%. Conclusion: Despite challenging and protracted complex humanitarian situation in the northwest Syria, the number of patients enrolled and the proportion who successfully completed the TB treatment is acceptable. However, these results are preliminary, as clinical outcomes were available only for the first and second cohorts of patients enrolled. Innovative solutions and flexibility in the execution and continued expansion of this promising project are imperative.